2019
DOI: 10.4491/eer.2019.374
|View full text |Cite
|
Sign up to set email alerts
|

Application of modified red mud in environmentally-benign applications: A review paper

Abstract: Red mud (RM) is a waste product that results from bauxite refining via the Bayer process. Its disposal remains an issue which raises significant environmental concerns, particularly if disposed on land or water bodies. Much research has been done on the use of red mud for environmentally-benign applications such as wastewater treatment, catalysis, the production of construction materials and glass ceramics, and for the recovery of metals. This paper reviews the current efforts made in the utilization of red mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 79 publications
(65 reference statements)
1
29
0
Order By: Relevance
“…Figure 13 demonstrates the influence of S:L ratio and concentration of the acid on the recovery degree of aluminum, titanium, iron, and scandium. As can be seen, the dissolution degree of Ti drastically grows up with an increase of acid concentration and S:L ratio that is consistent with equation (6). It has to be taken into account that an increase of S:L ratio led to a drop not only aluminum extraction degree, but also scandium extraction degree that accords with previous studies [63,64].…”
Section: Hpal Experiments With Variation Of Leaching Time S:l Ratio and Hcl Concentrationsupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 13 demonstrates the influence of S:L ratio and concentration of the acid on the recovery degree of aluminum, titanium, iron, and scandium. As can be seen, the dissolution degree of Ti drastically grows up with an increase of acid concentration and S:L ratio that is consistent with equation (6). It has to be taken into account that an increase of S:L ratio led to a drop not only aluminum extraction degree, but also scandium extraction degree that accords with previous studies [63,64].…”
Section: Hpal Experiments With Variation Of Leaching Time S:l Ratio and Hcl Concentrationsupporting
confidence: 89%
“…The lack of efficient processing technologies is the main reason why red mud is out of use and accumulated in special sludge storage facilities, which have an adverse impact on the environment and even have led to the technogenic catastrophe [3]. It has found that red mud is proved to be a promising material for the obtaining of coagulants and can be used as an adsorbent for heavy metals in wastewater; it can also be utilized in a wide range of catalytic applications [5], as well as for a production of various building materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of efficient processing technologies is the main reason why red mud is out of use and accumulated in special sludge storage facilities, which have an adverse impact on the environment and have even led to technogenic catastrophe [3]. It has found that red mud is proved to be a promising material for obtaining coagulants and can be used as an adsorbent for heavy metals in wastewater [5]; it can also be utilized in a wide range of catalytic applications [6], as well as for a production of various building materials [7]. Thus, a promising way for the extraction of valuable components from red mud is the reduction roasting with obtaining of magnetic iron concentrate and non-magnetic tailings enriched in aluminum, titanium and REEs followed by the treatment of the tailings by high-pressure hydrochloric acid leaching.…”
Section: Introductionmentioning
confidence: 99%
“…It is typically separated from other minerals through the Bayer process, which produces a large amount of inorganic waste. Globally, every tonne of alumina produced implies between 1 and 1.5 tonnes of red mud 1 . The waste deriving from the Bayer process, usually termed as “red mud,” is a caustic slurry, containing Al 2 O 3 (5‐30wt.%), SiO 2 (3‐50wt.%), and Fe 2 O 3 (5‐60wt.%) as major components, but also featuring toxic pollutants, in the form of heavy metal (Cr, Ni, Cu, Pb, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The handling of highly toxic constituents hinders but does not prevent red mud up‐cycling: multiple attempts to transform it into useful products have been reported 1–10 . Those based on vitrification treatment are generally favored in terms of stabilization of pollutants, 3–6 but some sustainability issues remain.…”
Section: Introductionmentioning
confidence: 99%